The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1118/1.3605471
|View full text |Cite
|
Sign up to set email alerts
|

A new clinical unit for digital radiography based on a thick amorphous Selenium plate: Physical and psychophysical characterization

Abstract: As normally happens with detector based on direct conversion, the system presents an excellent MTF. The improved efficiency caused by the thick layer allows getting good noise characteristics and DQE results better (about 10% on average) than many of the computed radiography (CR) systems and comparable to those obtained by the best systems for digital radiography available on the market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Many studies [2][3][4][5][6][7][8][9][10][11][12] have reported largely standardized methods to measure the physical performance of imaging systems based on the International Electrotechnical Commission IEC 62220-1 standard. 4 These studies were based on the metric-the detective quantum efficiency (DQE)-which reflects detector efficiency when forming an image using a limited number of x-ray photons, providing an input signalto-noise ratio (SNR) at a specific exposure level.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [2][3][4][5][6][7][8][9][10][11][12] have reported largely standardized methods to measure the physical performance of imaging systems based on the International Electrotechnical Commission IEC 62220-1 standard. 4 These studies were based on the metric-the detective quantum efficiency (DQE)-which reflects detector efficiency when forming an image using a limited number of x-ray photons, providing an input signalto-noise ratio (SNR) at a specific exposure level.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of our plugin have already been used in various published papers for achieving the physical characterization of several computed and digital radiography systems both for general radiography and for digital mammography. [15][16][17][18][19] A brief user manual is also available on the aforementioned website (www.medphys.it/downloads.htm) for helping users in realizing the basic operations with the software ("COQ: an ImageJ plugin for the physical characterization and quality checks of digital detectors").…”
Section: Resultsmentioning
confidence: 99%
“…8 However, the most interesting range analyzed for characterizing detectors for digital radiography is from about 1 μGy to an upper limit of around 10 μGy, as reported and considered by many authors. [9][10][11][12][13][14][15][16][17][18][19] Hence, in this paper we achieved the characterization of the clinical unit in the range 1-15 μGy.…”
Section: Methodsmentioning
confidence: 99%